2009
DOI: 10.1038/sj.bjc.6605437
|View full text |Cite
|
Sign up to set email alerts
|

Glycogen synthase kinase-3: a new therapeutic target in renal cell carcinoma

Abstract: BACKGROUND: Renal cell carcinoma (RCC) is highly resistant to chemotherapy because of a high apoptotic threshold. Recent evidences suggest that GSK-3b positively regulates human pancreatic cancer and leukaemia cell survival in part through regulation of nuclear factor (NF-kB)-mediated expression of anti-apoptotic molecules. Our objectives were to determine the expression pattern of GSK-3b and to assess the anti-cancer effect of GSK-3b inhibition in RCC. METHODS: Immunohistochemistry and nuclear/cytosolic fract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
101
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(117 citation statements)
references
References 34 publications
14
101
0
Order By: Relevance
“…GSK-3β has been reported as a candidate target in leukemia and other malignancies (13)(14)(15)(16)(17)(18). In this manuscript, we report a role for GSK-3α in human AML.…”
Section: Introductionmentioning
confidence: 72%
“…GSK-3β has been reported as a candidate target in leukemia and other malignancies (13)(14)(15)(16)(17)(18). In this manuscript, we report a role for GSK-3α in human AML.…”
Section: Introductionmentioning
confidence: 72%
“…Untreated 0.5 mM 1 mM 10 mM 20 mM (days) % % % % % ------------------------------------------------- -------------------------------------------------data, lithium effects can be assigned to GSK-3ß inhibition (32,33), rather than to a specific Wnt activation, even if this molecular pathway is altered by the drug in both cell lines. On the other hand, the clinical dose of 1 mM lithium elicits anti-neoplastic effects only in D283MED cells.…”
Section: -------------------------------------------------Timementioning
confidence: 99%
“…Dose and time-dependent SB216763 improved the cytotoxic effect against the two human urothelial carcinoma cell lines, UMUC3 and UMUC14, suggesting potential therapeutic uses for GSK3 inhibitors. 24 Bilim et al 25 showed that GSK3 inhibitors could decrease viability of renal cancer cell lines. Therefore, nuclear accumulation of GSK3 is a new promising marker of human renal cell carcinoma (RCC) cells.…”
mentioning
confidence: 99%
“…Therefore, nuclear accumulation of GSK3 is a new promising marker of human renal cell carcinoma (RCC) cells. 25 GSK3 is up-regulated in prostate cancer. 26 SB216763 was able to increase -catenin expression level in androgen receptor (AR) positive and negative cell lines.…”
mentioning
confidence: 99%